Argon‐Plasma Reinforced Superamphiphobic Fabrics. Issue 40 (1st September 2017) - Liu, Shuai; Zhou, Hua; Wang, Hongxia; Yang, Weidong; Shao, Hao; Fu, Sida; Zhao, Yan; Liu, Deqi; Feng, Zhihua; Lin, Tong
Abstract: A novel method for preparing durable superamphiphobic fabrics is reported, which involves preapplying a solution consisting of perfluoroalkyl acrylate, epoxide‐containing silane, and silica nanoparticles onto fabric and subsequent argon‐plasma treatment. The coated fabrics show superphobic to both water and oil fluids (surface tension >21.5 mN m −1 ). The coating is durable to withstand repeated laundries and multicycles of abrasion without apparently altering the superamphiphobicity. The coating is also very stable in boiling water, strong acid, and base, but has little effect on the fabric handle and air permeability. The argon‐plasma‐enhanced coating may offer a facile way to prepare durable superamphiphobic fabrics. Abstract : A fabric after precoating with a mixture of epoxide silane, perfluoroalkyl acrylate, and silica nanoparticles and subsequent argon‐plasma treatment shows high superamphiphobicity. The plasma‐treated coating is durable against repeated laundries, multicycles of abrasion, and boiling water, strong acid and base. The coating has little effect on the fabric handling and air permeability.